MATERIALITY - AN IMPORTANT METHOD AND TECHNIQUE FOR THE FINANCIAL AUDITING - Ndreca, Pjeter (European Scientific Journal, ESJ, 2013)
The purpose of this press article is: - to address the application of materiality in nature as one of the best techniques that provides assurance in auditing the financial statements, - to precise the concept of materiality and his definition, - to explain the relationship and difference that exist between materiality and the auditing risk, - to explain the procedures to be followed in determining the assurance factor, - to prove that the best efficiency in auditing financial statements, can be achieved if we apply materiality in nature, - to explain the nature of indicators and the method of calculating, - to illustrate through a practical case the methodology for calculating the indicators of materiality in nature and to interpret the data in comparison of indicators.